Enhancing the circular economy with nature-based solutions in the built urban environment: green building materials, systems and sites. Issue 1 (3rd December 2019) - Pearlmutter, David; Theochari, Dimitra; Nehls, Thomas; Pinho, Pedro; Piro, Patrizia; Korolova, Alisa; Papaefthimiou, Spiros; Mateo, Mari Carmen Garcia; Calheiros, Cristina; Zluwa, Irene; Pitha, Ulrike; Schosseler, Paul; et al.
Abstract: The objective of this review paper is to survey the state of the art on nature-based solutions (NBS) in the built environment, which can contribute to a circular economy (CE) and counter the negative impacts of urbanization through the provision of ecosystem services. NBS are discussed here at three different levels: (i) green building materials, including biocomposites with plant-based aggregates; (ii) green building systems, employed for the greening of buildings by incorporating vegetation in their envelope; and (iii) green building sites, emphasizing the value of vegetated open spaces and water-sensitive urban design. After introducing the central concepts of NBS and CE as they are manifested in the built environment, we examine the impacts of urban development and the historical use of materials, systems and sites which can offer solutions to these problems. In the central section of the paper we present a series of case studies illustrating the development and implementation of such solutions in recent years. Finally, in a brief critical analysis we look at the ecosystem services and disservices provided by NBS in the built environment, and examine the policy instruments which can be leveraged to promote them in the most effective manner – facilitating the future transition to fully circular cities.